Analisis Ekonomi Rumah Tangga Petani Tembakau di Desa Kadakajaya Kecamatan Tanjungsari Kabupaten Sumedang - Annisa, Ravena Risna; Heryanto, Mahra Arari (Universitas Galuh, 2026)
Tobacco farming remains a primary source of livelihood for farmers in Kadakajaya Village, Tanjungsari District, Sumedang Regency. However, income from tobacco alone is insufficient to meet household needs, as it only provides returns once a year. Moreover, tobacco farmers only get income from tobacco farming once a year. In fact, household expenses are incurred every day, every week, and sometimes there is a very urgent time before the harvest arrives, both expenses in the form of production costs and daily needs. The household economy is a complex and interconnected system so that the system thinking approach can be applied to analyze the dynamics of the household economy of tobacco farmers, which is visualized using the causal loop diagram (CLD) analysis tool. The results of the study showed that the five tobacco farmer households have income outside of tobacco farming to meet their household needs; each household has a different behavioral patterns of income, expenses, and household cash. Although tobacco farmers say that their household needs are still lacking to meet daily needs, tobacco farmer households are above the poverty line. Based on the research results, the suggestions that can be recommended are that each household should record finances separately between household finances and farming, tobacco farmers are expected to be able to utilize time outside of farming to diversify income, and this study still has limitations in the number of informants and the scope of the area so that further researchers are expected to be able to develop this study with a wider number of respondents and coverage area.